Canine serological survey and dog culling ant its relationship with human visceral leishmaniasis in an endemic urban area - Bermudi, Patricia Marques Moralejo; Costa, Danielle Nunes Carneiro Castro; Nunes, Caris Maroni [UNESP]; Tolezano, Jose Eduardo; Hiramoto, Roberto Mitsuyoshi; Rodas, Lilian Aparecida Colebrusco; Cipriano, Rafael Silva; Blangiardo, Marta; Chiaravalloti-Neto, Francisco (Springer Nature, 2020)
Background: Visceral leishmaniasis is an important but neglected disease that is spreading and is highly lethal when left untreated. This study sought to measure the Leishmania infantum seroprevalence in dogs, the coverage of its control activities (identification of the canine reservoir by serological survey, dog culling and insecticide spraying) and to evaluate its relationship with the occurrence of the disease in humans in the municipalities of Araçatuba and Birigui, state of São Paulo, Brazil. Methods: Information from 2006 to 2015 was georeferenced for each municipality and modeling was performed for the two municipalities together. To do this, latent Gaussian Bayesian models with the incorporation of a spatio-temporal structure and Poisson distribution were used. The Besag-York-Mollie models were applied for random spatial effects, as also were autoregressive models of order 1 for random temporal effects. The modeling was performed using the INLA (Integrated Nested Laplace Approximations) deterministic approach, considering both the numbers of cases as well as the coverage paired year by year and lagged at one and two years. Results: Control activity coverage was observed to be generally low. The behavior of the temporal tendency in the human disease presented distinct patterns in the two municipalities, however, in both the tendency was to decline. The canine serological survey presented as a protective factor only in the two-year lag model. Conclusions: The canine serological coverage, even at low intensity, carried out jointly with the culling of the positive dogs, suggested a decreasing effect on the occurrence of the disease in humans, whose effects would be seen two years after it was carried out.
Keywords: Brazil; Control measures; Ecological study; Visceral leishmaniasis